Elevated fear states facilitate ventral hippocampal engagement of basolateral amygdala neuronal activity - Ritger, Alexandra C.; Parker, Rachel K.; Trask, Sydney; Ferrara, Nicole C. (Frontiers in Behavioral Neuroscience, 2024)
Fear memory formation and retention rely on the activation of distributed neural circuits. The basolateral amygdala (BLA) and ventral hippocampus (VH) in particular are two regions that support contextual fear memory processes and share reciprocal connections. The VH→BLA pathway is critical for increases in fear after initial learning, in both fear renewal following extinction learning and during fear generalization. This raises the possibility that functional changes in VH projections to the BLA support increases in learned fear. In line with this, fear can also be increased with alterations to the original content of the memory via reconsolidation, as in fear elevation procedures. However, very little is known about the functional changes in the VH→BLA pathway supporting reconsolidation-related increases in fear. In this study, we used in vivo extracellular electrophysiology to examine the functional neuronal changes within the BLA and in the VH→BLA pathway as a result of fear elevation and standard fear retrieval procedures. Elevated fear expression was accompanied by higher BLA spontaneous firing compared to a standard fear retrieval condition. Across a range of stimulation frequencies, we also found that VH stimulation evoked higher BLA firing following fear elevation compared to standard retrieval. These results suggest that fear elevation is associated with an increased capacity of the VH to drive neuronal activity in the BLA, highlighting a potential circuit involved in strengthening existing fear memories.